HE 220 - Intro: Epidemiology/Health Data Analysis Textbook - Kristi Murphey (Linn-Benton Community College, 2019)
Introduction to epidemiology and the use of elementary statistics for students in health-related studies. This course is designed to provide preparatory background for taking subsequent course in epidemiology and health data analysis offered by the Department of Public Health. This course introduces measure of disease frequency, analytical epidemiology, study designs, experimental design, and basic elements of descriptive statistics and inferential statistics.